Circularly polarized microstrip antenna with bidirectional radiation using dual-layered arrow-shape slot perturbation for CubeSat application - Lee, Sunghee; Pyo, Seongmin; Kim, Jae Hyun (Microwave and Optical Technology Letters, 2018)
This article proposes a novel circularly polarized microstrip antenna supported with bidirectional opposite-sense radiation using a dual-layered arrow-shaped slot perturbation. Unlike a conventional perturbation which is etched only on one side, the arrow-shaped slot perturbation of the proposed antenna is divided into two diagonal half-arrows and etched on both the top and bottom side. Consequently, the counter-clockwise rotation of electric surface currents at the radiator side for right-handed circular polarization and the clockwise rotation of those at the ground side for left-handed circular polarization are successfully achieved. The measurement results of the proposed antenna show good agreement with the simulations of reflection coefficients, axial ratios, antenna gains, and radiation patterns.
Keywords: arrow-slot; Bidirectional radiation patterns; Circularly polarized microstrip antennas; Clockwise rotation; Counter clockwise rotation; dual-layered loading perturbation; opposite polarization sense; Surface current; arrow-slot; bidirectional radiation pattern; circular polarization; dual-layered loading perturbation; opposite polarization sense